2021
DOI: 10.1016/j.jbc.2021.101147
|View full text |Cite
|
Sign up to set email alerts
|

Deconvolution of multiplexed transcriptional responses to wood smoke particles defines rapid aryl hydrocarbon receptor signaling dynamics

Abstract: The heterogeneity of respirable particulates and compounds complicates our understanding of transcriptional responses to air pollution. Here, we address this by applying precision nuclear run-on sequencing and the assay for transposase-accessible chromatin sequencing to measure nascent transcription and chromatin accessibility in airway epithelial cells after wood smoke particle (WSP) exposure. We used transcription factor enrichment analysis to identify temporally distinct roles for ternary response factor–se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…We previously applied a combination of nascent transcript sequencing using Precision Run-on sequencing (PRO-seq) and chromatin profiling using the assay for transposase accessible chromatin with sequencing (ATAC-seq) to define the mechanistic basis for the immediate early effects of WSP on airway epithelial cells. Our data indicated that acute exposure to particulate matter under highly controlled experimental conditions results in broad transcriptional and epigenetic responses (17), including induction of NFkB activity. Furthermore, PRO-seq provides an indirect measure of the activity of transcriptional regulatory elements (TREs) based on associated enhancer RNA levels.…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…We previously applied a combination of nascent transcript sequencing using Precision Run-on sequencing (PRO-seq) and chromatin profiling using the assay for transposase accessible chromatin with sequencing (ATAC-seq) to define the mechanistic basis for the immediate early effects of WSP on airway epithelial cells. Our data indicated that acute exposure to particulate matter under highly controlled experimental conditions results in broad transcriptional and epigenetic responses (17), including induction of NFkB activity. Furthermore, PRO-seq provides an indirect measure of the activity of transcriptional regulatory elements (TREs) based on associated enhancer RNA levels.…”
Section: Introductionmentioning
confidence: 78%
“…We first employed PRO-seq to characterize gene transcriptional responses to APM in SAECs. Our previous study demonstrated marked temporal variation in transcriptional responses within the first two hours of particulate exposure (26). Therefore, we anticipated nascent transcription after 20 hours of exposure would represent a steady-state response to APM.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations